Effect of cellulose crystallinity on the formation of a liquid intermediate and on product distribution during pyrolysis - Wang, Zhouhong; McDonald, Armando; Westerhof, Roel; Kersten, Sascha; Cuba-Torres, Christian; Ha, Su; Pecha, Brennan; Garcia-Perez, Manuel (Elsevier, 2013)
The effect of cellulose crystallinity on the formation of a liquid intermediate and on its thermal degradation was studied thermogravimetrically and by Py-GC/MS using a control cellulose (Avicel, crystallinity at 60.5%) and ball-milled Avicel (low cellulose crystallinity at 6.5%). The crystallinity of the materials studied was quantified by XRD and FTIR. Thermogravimetric analyses (TGA) show the samples with lower crystallinity start to degrade at lower temperatures, exhibiting sharper DTG curves and lower thermal degradation activation energies. Scanning electron microscopy (SEM) studies of the solid residues formed in TGA tests showed that, while the conversion of the ball-milled cellulose (mostly amorphous cellulose)occurs through the formation of a liquid intermediate, in the conversion of the control the fibrous structure is conserved. Py-GC/MS studies showed major differences in the thermal behavior of the samples studied. At 300 degrees C, amorphous cellulose yielded more levoglucosan. At temperatures between 350 and 450 degrees C, higher yields of mono-anhydrosugars (levoglucosan and levoglucosenone) were obtained with the samples with higher crystallinity (control). The ball-milled cellulose produced more 5-(hydroxymethyl) furfural, 5-methylfurfural and furfural. The higher yields of these compounds are due to the acceleration of dehydration reactions when a liquid phase intermediate was formed. Fragmentation reactions responsible for the formation of light compounds (glycoaldehyde, acetic acid, methyl-vinyl-ketone and acetol)and the reactions responsible for the formation of cyclopentane do not seem to be affected by cellulose crystallinity and by the formation of a liquid intermediate.